Digital written discourse - Mansor, Noraien; Abd Rahim, Normaliza (Serials Publications, 2017)
The booming of new technologieshelps people in using the latest technology in getting useful information in their everyday lives. Through new technologies as in digital media, there will be communication taken place. The study focuses on digital written discourse in instagram. The objectives of the study were to identify and discuss the presupposition, reference, implicature and inference of discourse analysis in instagram captions among twenty subjects involved ornamely known as instagrammers. Brown & Yule (1983) discourse analysis theory was used to analyse the data. Captions from twenty instagrams were taken and related extracts were analysed. The results of the study revealed that the captions were understood when discourse analysis were discussed and explained. The instagrammers were able to use presupposition, reference, implicature and inference in their instagram. The message were well understood and delivered successfully. The subjects involved seemed to have build their confidence in writing when there were response pertaining to the captions. It is hoped that further studies will focus on other linguistics approaches for analysing the captions.